COMBINATION OF FOLINIC ACID AND PSYCHOTHERAPY AS A MODERN METHOD OF TREATMENT OF AUTISM SPECTRUM DISORDER – A SYSTEMATIC REVIEW - Bartosz Skorupski; Magdalena Próchnicka; Jakub Lipiec; Natalia Strumnik; Oliwia Sójkowska-Sławińska; Anna Leśniewska; Patryk Macuk; Michał Gniedziejko; Jakub Roszak; Paulina Bernecka (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Autism spectrum disorder (ASD) is a complex disorder of the development and functioning of the central nervous system. The onset of the disorder is usually in early childhood. It is characterized by difficulty in reading and communicating feelings, disturbances in the ability to build interpersonal relationships, as well as impoverishment and stereotypical behavior. Materials and methods: This article, based on a PubMed review of available research, examines the impact of folinic acid and Picture Exchange Communication System therapy on improving communication in children with ASD. Results: In the first of the reported studies, a double-blind study was conducted - 48 children with an autism spectrum disorder and language impairment were randomized to receive 12 weeks of high dose folinic acid or placebo. The improvement in verbal communication, as measured by a standardized ability-appropriate tool, was significantly greater in participants receiving folinic acid compared to those receiving placebo. In the second test, 20 children were qualified for the study. The program consisted of 24 sessions of individual speech therapy and followed the six phases proposed in the PECS training manual. All children were clinically assessed by a team of child psychiatrists, neuropsychologists and speech therapists. After the study was completed, there was a clear increase in children’s understanding of all instructions compared to the initial phase of the program. Conclusions: The therapies described above improve the communication skills of patients on the autism spectrum. Not only does it provide an augmentative or alternative communication tool for children to express their needs, it also significantly improves understanding of contextual information.